Effectiveness of Health Education in Reducing Plasmodium Vivax Malaria Recurrence in Sentani Papua (Indian Journal of Public Health Research & Development, 2020)
Objectives: Plasmodium vivax is a type of Plasmodium that is difficult to eliminate because it has ahypnozoite phase in the human liver and responsible for malaria recurrence[1]. Health education is oneof method that can be used to improve adherence to primaquine treatment. In doing so, the vivax malariarecurrence rate can be decreased significantly. The aim of this study was to examine the effectiveness ofhealth education in reducing Plasmodium vivax malaria recurrence.Method: A quasi-experimental method was conducted in January-August 2019 at Sentani Papua. Patientsfrom community health care had been diagnosed with P.vivax malaria by microscopy, age ? 1 year, treatedaccording to national standards with DHP for 3 days and primaquine 14 days, were recruited. Patients weredivided into 2 groups, namely, the standard therapy group (ST) and the standard therapy group with healtheducation (HE) group. Then patients were followed-up for 90 days.Results: Among 105 patients, 50 were in the ST group and 55 were in the HE group. Patients recoveredwithout serious adverse effects. The incidence rate of recurrence in the HE group was much lower comparedto the ST group (2.04/10,000 person-days vs 21.51/10,000 person-days, p
Keywords: Health Education, Recurrence of malaria, Papua.